2022
DOI: 10.3897/phytokeys.206.75971
|View full text |Cite
|
Sign up to set email alerts
|

New Piper species from the eastern slopes of the Andes in northern South America

Abstract: We describe four new species of Piper from the Amazonian slopes of the northern Andes. Piper hoyoscardozii is distinguished from similar climbing species, P. dryadum and P. flagellicuspe, by its longer peduncles. The Amazonian species Piper indiwasii is distinguished from P. scutilimbum from Panama and northern Colombia by the narrowly spatulate leaf base extension. Piper nokaidoyitau is characterised by the presence of larger leaves and longer spikes than similar species, P. anonifolium and P. hostmannianum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…To the trained specialist, new Piper species are a common finding in the tropical forests, or even in the undetermined piles in the most important herbaria around the world. Additionally, molecular phylogenetics have confirmed the clade (subgeneric) affiliation of new species ( Bornstein et al 2014 ; Tepe et al 2014 ; Trujillo et al 2022 ). During our exploration to Serranía de las Quinchas we have identified a few undescribed species, one of the stands-out because it has peltate leaves, a characteristic rarely observed in the genus.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…To the trained specialist, new Piper species are a common finding in the tropical forests, or even in the undetermined piles in the most important herbaria around the world. Additionally, molecular phylogenetics have confirmed the clade (subgeneric) affiliation of new species ( Bornstein et al 2014 ; Tepe et al 2014 ; Trujillo et al 2022 ). During our exploration to Serranía de las Quinchas we have identified a few undescribed species, one of the stands-out because it has peltate leaves, a characteristic rarely observed in the genus.…”
Section: Introductionmentioning
confidence: 79%
“…Molecular phylogenetics demonstrated that Trianaeopiper is not monophyletic, revealing that the diagnostic character axillary inflorescence – which are shortened sympodial branches, is convergent ( Jaramillo and Callejas-Posada 2004 ). Similarly, molecular phylogenetics have further supported that Piper species with peltate leaves are part of at least four Neotropical Piper clades ( Trujillo et al 2022 ). Piper classification, evolution and ecological studies have been greatly enriched with molecular phylogenetics.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Among these, Piper is the most diverse and representative genus, encompassing ca. 2600 species ( Trujillo et al, 2022 ). Besides pungent compounds, many Piper species produce essential oils and are hence highly aromatic, explaining their use for cooking and medicinal purposes ( Ruiz-Vásquez et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%